Because its power remains naturalized: introducing the settler colonial determinants of health - Wispelwey, Bram; Tanous, Osama; Asi, Yara; Hammoudeh, Weeam; Mills, David (Frontiers in Public Health, 2023)
Indigenous people suffer earlier death and more frequent and severe disease than their settler counterparts, a remarkably persistent reality over time, across settler colonized geographies, and despite their ongoing resistance to elimination. Although these health inequities are well-known, they have been impervious to comprehensive and convincing explication, let alone remediation. Settler colonialism, the focus of a fast-growing multidisciplinary and interdisciplinary field, is a promising candidate to rectify this impasse. Settler colonialism’s relationship to health inequity is at once obvious and incompletely described, a paradox arising from epistemic coloniality and perceived analytic challenges that we address here in three parts. First, in considering settler colonialism an enduring structure rather than a past event, and by wedding this fundamental insight to the ascendant structural paradigm for understanding health inequities, a picture emerges in which this system of power serves as a foundational and ongoing configuration determining social and political mechanisms that impose on human health. Second, because modern racialization has served to solidify and maintain the hierarchies of colonial relations, settler colonialism adds explanatory power to racism’s health impacts and potential amelioration by historicizing this process for differentially racialized groups. Finally, advances in structural racism methodologies and the work of a few visionary scholars have already begun to elucidate the possibilities for a body of literature linking settler colonialism and health, illuminating future research opportunities and pathways toward the decolonization required for health equity.